Commodity price fluctuations and their impact on monetary and fiscal policies in Western and Central Africa - Uwe Böwer; André Geis; Adalbert Winkler (European Central Bank (ECB), 2007)
Commodity prices play an important role in economic developments in most of the 24 Western and Central African (WCA) countries covered in this paper. It is confirmed that in the light of rising commodity prices between 1999 and 2005, net oil exporters recorded strong growth rates while net oil-importing countries – albeit benefiting from increases in their major non-oil commodity export prices – displayed somewhat lower growth. For most WCA economies, inflation rates appear less affected by commodity price changes and more determined by exchange rate regimes as well as monetary and fiscal policies. While passthrough effects from international to domestic energy prices were significant, notably in oilimporting countries, second-round effects on overall prices seem limited. Governments of oil-rich countries reacted prudently to windfall revenues, partly running sizable fiscal surpluses. A favourable supply response to rising spending as well as sterilisation efforts and increasing money demand also helped to dampen inflationary pressures. However, substantial excess reserves of commercial banks reflect challenges in financial sector developments and the effectiveness of monetary policy in many WCA countries. Given currently widelyused fixed exchange rate regimes, fiscal policy will continue to carry the main burden of macroeconomic adjustment and of sustaining non-inflationary growth, which remains the key policy challenge facing WCA authorities.
Keywords: 330; Geldpolitik; Finanzpolitik; Rohstoffpreis; Westafrika; Zentralafrika